2011
DOI: 10.1111/j.1447-0594.2010.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience of elderly Spanish men with an implantable cardioverter‐defibrillator

Abstract: Elderly recipients can end up "clinging on" to customs as they are felt to define the recipient's identity and utility within their social and personal context. Their partner is of huge significance for elderly recipients. The geriatric health personnel must contribute to promote and maintain activities of daily living in elderly. Future qualitative studies taking an in-depth look at the experience and readjustment process of elderly recipients and the relationship among older people and technological equipmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 48 publications
(138 reference statements)
0
19
0
Order By: Relevance
“…There was also apprehension over resuming sexual activity as the majority feared of shocks hurting their partners [18, 20, 23, 43]. Few studies reported on the sexual concerns associated with ICD, possibly because the participants were uncomfortable in bringing up such sensitive topics with the researchers.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There was also apprehension over resuming sexual activity as the majority feared of shocks hurting their partners [18, 20, 23, 43]. Few studies reported on the sexual concerns associated with ICD, possibly because the participants were uncomfortable in bringing up such sensitive topics with the researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Anger with one’s limitations and resentment towards ICD [15, 20, 38] were also observed. Many still harboured insecurities over the device failing or battery depleting [20, 38, 44] as well as the uncertainties that accompany arrhythmias [14] or awaiting ICD discharges [43]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations